Characteristics of Sand-driving Wind Regime and Sediment Transport at Northeast Edge of Bayan Wendur Desert - Zhang Hao; Dang Xiaohong; Liu Yang; Meng Zhongju; Guo Chunhui; Zhang Ge (Shuitu baochi tongbao)
[Objective] The characteristics of sand-driving wind and sand-transporting potential are the key indexes for evaluating the regional wind energy environment. The change characteristics of the wind regime and transport potential of sand-driving wind in the Northeast Bayan Wendur Desert were analyzed, the dynamic wind characteristics and the intensity of the wind energy activity near the ground were revealed, and the regional wind energy environment was evaluated, in order to provide a theoretical basis for the study of sand movement and scientific options for sand movement prevention and control. [Methods] Wind data were acquired from a meteorological station on the northeast edge of the Bayan Wendur Desert from 2017 to 2021, and the characteristics of the sand-driving wind and sediment transport potential in the region were analyzed. [Results] ① The annual average frequency of sand-driving wind was 43.70%, and the average sand-driving wind speed was 7.57 m/s, both of which were the highest in spring. The sand-driving winds in different seasons and the annual average were mainly westerly (W, WSW, SW) and southerly (S, SSE, SE). ② The annual average sediment transport potential (DP) was 68.36 VU. The composite sediment transport potential (RDP) was 29.39 VU. The wind direction variability index (RDP/DP) was 0.43. The composite sediment transport potential direction (RDD) was 91.33°. The DP and RDP in spring were significantly greater than in other seasons. ③ The influence of the average wind speed on the sediment transport potential in the study area was greater than the frequency of the wind speed. The intensity of sand movement was mainly determined by wind speed. [Conclusion] The northeast edge of the Bayan Wendur Desert generally belongs to a low wind energy environment. The surface sand material is transported eastward throughout the year. Spring is the most important period of wind and sand activity. June is the key period for the construction of artificial protective forests and aerial-seeding afforestation for sand control. We recommend that the direction of planting protective forest shelterbelts and for aerial seeding of forest seeds be perpendicular to the direction of sand transport potential so as to block the continuous eastward movement of sand.